Run, Rose, run : a novel - Parton, Dolly; Patterson, James, 1947-; OverDrive, Inc. (New York : Little, Brown and Company, 2022)
"The biggest novel of 2022! A thriller about a young musician on the run, authored by America's #1 most beloved entertainer and its #1 bestselling author. Every song tells a story. She's a star on the rise, singing about the hard life behind her. She's also on the run. Find a future, lose a past. Nashville could be the place she claims her destiny-or where her yesterdays collide with her tomorrows. Run, Rose, Run is a novel glittering with danger and stardust, by the queen of country and the king of suspense"--.
Electronic book.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Novels; Electronic books; Thriller fiction